Socialization and Training on SGX SICOM for Rubber Farmers in Lalang Sembawa Village, South Sumatera, Indonesia - Hafiz Hidayahtullah; Amelia Resta Maharani; Dita Aura Silviyanti; Lira Virna; Susi Handayani; E. Emilda; Muhammad Wadud (Golden Ratio of Data in Summary, 2026)
The SGX SICOM training was held in Lalang Sembawa Village, Banyuasin Regency, South Sumatra, Indonesia, as a community service activity aimed at increasing the understanding and digital literacy of rubber farmers towards the mechanism of determining the price of natural rubber in the international market. Indonesia, as one of the world's largest natural rubber producers, still faces the challenge of low price literacy among farmers, which weakens their bargaining position with buyers. This activity is designed to bridge the information gap through focus group discussion (FGD) methods, interviews, delivery of interactive materials, and the practice of directly accessing price data on the Singapore Commodity Exchange (SGX SICOM). A total of nine farmers were selected purposively based on their experience and active involvement in rubber cultivation and marketing. Evaluations were carried out using pre-tests and post-tests to measure the improvement of participants' knowledge and skills, with descriptive-quantitative analysis to assess the effectiveness of the activities. The results showed a significant improvement in three key indicators, namely understanding of price determinants increased from 20% to 35%, knowledge of SGX SICOM from 17% to 26%, and the ability to search and analyze rubber prices from 9% to 15%. This activity has proven to be effective in increasing market literacy, price analysis skills, and digital independence of rubber farmers, while providing a positive socio-economic impact in the form of increasing bargaining power and readiness to face global rubber price dynamics.